ENSAYO DE DIFERENTES TIPOS DE CONTENEDORES PARA Q.ILEX, P.HALEPENSIS, P.PINASTER Y P.PINEA: RESULTADOS DE VIVERO (II Congreso Forestal Español, 1997)
The influence of 16 of the most commonly utilised containers on seedling characteristics of Quercus ilex, Pinus pinea, P. halepensis and P. pinaster have been analysed. Studied plant features -height, diameter, shoot and root dry weight, and number of branches- were correlated with container dimensions. Observations on sorne practical problems in several containers and their suitability for forest plant production are given.

ENSAYO DE TRATAMIENTOS HERBICIDAS EN CULTIVO DE TRES ESPECIES FORESTALES (P. halepensis, P. nigra y Q. ilex) EN VIVERO (II Congreso Forestal Español, 1997)
Weeds are one of the problems which more economic costs originates in forest nurseries due to their effect on crop growth. In spite of this, the effect of weeds on forest seedlings and their control in the nursery have not been much studied. In this study we have analysed the ability of five herbicides (Pendimethalin, Propizamide, Napropamide, Oxyflurofen and Simazine) in controlling weeds and their possible harmful effect on two Pinus species (Pinus halepensis, P. nigra ) and Quercus ilex in the nursery. Pendimethalin and Propizamide damaged seriously all tree species while Napropamide and Oxyflourfen did not produce any harmful effect and did not control effectively weeds. Simazine controlled weeds not affecting tree seedlings although it had to be applied periodically to mantain its effect on weeds.

INFLUENCIA DEL TAMAÑO DE LA SEMILLA Y DIFERENTES DOSIS DE FERTILIZACION SOBRE EL CRECIMIENTO Y SUPERVIVENCIA EN CAMPO DE CUATRO ESPECIES FORESTALES (II Congreso Forestal Español, 1997)
The effect of different fertilization doses on the growth in nursery and the field performance were assessed in Q.ilex, P.pinea, P.pinaster and P.sylvestris, wich differ in their seed size. Growth in nursery and results in the field showed marcked differences between fertilized and unfertilized treatments. Smaller seed species are more dependent on fertilization than larger seed species.

PLANTACIÓN Y SIEMBRA DE Quereus ilex L.: EFECTOS DE LA PREPARACIÓN DEL TERRENO Y DE LA UTILIZACIÓN DE PROTECTORES EN LA SUPERVIVENCIA DE PLANTAS (II Congreso Forestal Español, 1997)
In a first experiment the effect of two tillage treatments, a deep mechanical tillage and no tillage, on the survival of seeded Quercus ilex seedlings was analysed. In a second experiment the influence of acorn seeding versus plantation of containerized seedling, as well as the effect of two types of treeshelters (with and without lateral ventilation holes) and treeshelter removal in summer on the survival of Q. ilex seedlings was studied. Microclimate inside treeshelters containing seedlings was also measured along a typical summer day. Deep tillage increased germination and survival in comparison with untilled treatment. Temperature and leaf to air vapor pressure deficit was higher inside the treeshelters, specially in those without wholes, than outside. In spite of this fact, both treeshelter types, and particularIy those with lateral ventilation holes, exhibited a higher survival percentages than the control without treeshelter. Neither acorn seeding nor the removal of treeshelters in summer improved survival. significantly.